THE ROLE OF DIPLOMATIC RELATIONS ON CONFLICT RESOLUTION IN SOUTH SUDAN - Alier, Dr. Gabriel; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
The study investigated the investigated the role of diplomatic relation on conflict resolution in south Sudan The major findings of the study were that there is a significant positive correlation between; Diplomatic relations on conflict resolution (r = 0.632, P-value < 0.01), conflict resolution (r = 0.512, P-value < 0.01) and the attributes explained 59% of the variance of Conflict (R Square =.518) as the level to which they can predict the level of Conflict resolution in State of South Sudan. Such that unit change in Diplomatic relations processes will contribute to a change in the The study recommends that the State and Country leaders should develop diplomatic relations with other international communities that aim at empowering people with education values and